Strain-Dependent Photoacoustic Characteristics of Free-Standing Carbon-Nanocomposite Transmitters - Muhammad Faraz; Muhammad Awais Abbasi; Donghee Son; Changhwan Shin; Kyu-Tae Lee; Sang Min Won; Hyoung Won Baac (Sensors, 2022)
In this paper we demonstrate strain-dependent photoacoustic (PA) characteristics of free-standing nanocomposite transmitters that are made of carbon nanotubes (CNT) and candle soot nanoparticles (CSNP) with an elastomeric polymer matrix. We analyzed and compared PA output performances of these transmitters which are prepared first on glass substrates and then in a delaminated free-standing form for strain-dependent characterization. This confirms that the nanocomposite transmitters with lower concentration of nanoparticles exhibit more flexible and stretchable property in terms of Young’s modulus in a range of 4.08–10.57 kPa. Then, a dynamic endurance test was performed revealing that both types of transmitters are reliable with pressure amplitude variation as low as 8–15% over 100–800 stretching cycles for a strain level of 5–28% with dynamic endurance in range of 0.28–2.8%. Then, after 2000 cycles, the transmitters showed pressure amplitude variation of 6–29% (dynamic endurance range of 0.21–1.03%) at a fixed strain level of 28%. This suggests that the free-standing nanocomposite transmitters can be used as a strain sensor under a variety of environments providing robustness under repeated stretching cycles.